Исследование процессов минералообразования барийсодержащих цементов на основе моноалюмината и гексаферрита бария - Иващенко, М. Ю.; Шабанова, Галина Николаевна; Ворожбиян, М. И.; Костыркин, О. В.; Цапко, Наталия Сергеевна (НТУ "ХПИ", 2014)
Исследованы процессы фазообразования барийсодержащих цементов на основе композиций системы ВаО – Аl₂О₃ – Fе₂О₃. В полученных образцах определили наличие свободного оксида бария, что дало возможность рассчитать степень превращения вещества и определить константу скорости реакции минералообразования для каждой температуры. С привлечением рентгенофазового анализа установлена последовательность образования фаз в сырьевой смеси. Полученные результаты позволяют осуществлять целенаправленный синтез фаз в системе ВаО – Аl₂О₃ – Fе₂О₃ и дают возможность технологического регулирования соотношения фаз при синтезе барийсодержащих цементов на основе моноалюмината и гексаферрита бария.

The processes of barium containing cements based on ВаО – Аl₂О₃ – Fе₂О₃ system compositions have been studied. The availability of free baryta has been determined in the obtained samples, that allowed us to calculate the degree of transubstantiation and to determine the constant of mineral formation reaction speed for each temperature. In order to prove the conducted research concerning the smoothness of baryta fixation and the formation of mono-aluminate and hexaferrite of barium under the specified temperatures and isothermic soakings, X-ray analysis of cakes has been conducted. The phase formation processes in barium containing cement take place at the expense of the reactions in a solid phase, the speed of which is described satisfactorily by Ginstling-Brounshtein equation. The technological parameters of barium containing cement synthesis on the base of ВаО – Аl₂О₃ – Fе₂О₃ system compositions have been determined. The obtained results allow performing purposeful phase synthesis in ВаО – Аl₂О₃ – Fе₂О₃ system and make it possible to regulate technologically phase relation under the synthesis of barium containing cements based on mono-aluminate and hexaferrite of barium.
The study of the processes of barium-containing cement mineral formation based on monoaluminat and barium hexaferrite
Keywords: минералообразование; сырьевые смеси; цемент; механизм фазообразования; степень превращения; моноалюминат бария; гесаферрита бария; cement; phase formation mechanism; degree of transubstantiation; reaction speed; mono-aluminate of barium; hexaferrite of barium